2016
DOI: 10.1017/s0007485316000493
|View full text |Cite
|
Sign up to set email alerts
|

Habitat management of organic vineyard in Northern Italy: the role of cover plants management on arthropod functional biodiversity

Abstract: The effect of cover plants on arthropod functional biodiversity was investigated in a vineyard in Northern Italy, through a 3-year field experiment. The following six ground cover plants were tested: Sweet Alyssum; Phacelia; Buckwheat; Faba Bean; Vetch and Oat; control. Arthropods were sampled using different techniques, including collection of leaves, vacuum sampling and sweeping net. Ground cover plant management significantly affected arthropod fauna, including beneficial groups providing ecosystem services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…The beneficial effects of covers on carabids and staphylinids have been extensively reported [45,71,72], while in the case of spiders the results are more variable. Several studies have reported an increase in the abundance of spiders on the ground in orchards with a vegetation cover [73][74][75], while in other studies, a non-significant effect in comparison to bare ground was registered [45,63]. The scelionids were another group of insects that benefited from the sown cover.…”
Section: Discussionmentioning
confidence: 93%
“…The beneficial effects of covers on carabids and staphylinids have been extensively reported [45,71,72], while in the case of spiders the results are more variable. Several studies have reported an increase in the abundance of spiders on the ground in orchards with a vegetation cover [73][74][75], while in other studies, a non-significant effect in comparison to bare ground was registered [45,63]. The scelionids were another group of insects that benefited from the sown cover.…”
Section: Discussionmentioning
confidence: 93%
“…Experiments carried out in the South of France, showed that predatory mites were present on herbaceous cover plants; however the main species encountered were not those occurring on vines (Tixier et al, 2015). As in (Burgio et al, 2016), the densities of predatory mites were usually higher in vineyards with cover crop than in vineyards without cover crops. Another hypotheses than simple reservoir effects can thus be drawn: (i) effect of cover crop pollen deposited on the vine leaves, (ii) effect of micro-climate conditions in vineyards managed with cover crops and/or (iii) effect of cover crop on vine physiology.…”
Section: Cover Crops/ground Covermentioning
confidence: 88%
“…Effects other than the reservoir role can also exist. Burgio et al (2016) studied predatory mite communities in vineyards managed with several cover crops. They observed higher predatory mite densities on vines managed with ground cover.…”
Section: Cover Crops/ground Covermentioning
confidence: 99%
“…Recently, applications of synthetic plant volatiles as attractants for beneficial insects were tested by field studies (James & Price, 2004; Simpson et al ., 2011 a ; Lucchi et al ., 2017). Moreover, the use of cover/plants management is considered an agroecological technique to enhance the vineyard functional biodiversity (Duso et al ., 1993, 2004, 2012; Gurr et al ., 2007; Thomson & Hoffmann, 2007; Altieri et al ., 2010; Burgio et al ., 2016). For this reason, using elicitors as an attractant for natural enemies and flowering plants to provide them food and shelter, represents potential to reduce the lag between the build-up of natural enemies and taking control of pests (Simpson et al ., 2011 b ).…”
Section: Discussionmentioning
confidence: 99%